Strategic Leadership for Change and Innovation in the World of Islamic Education - Muhammad Durrin Ni'am; Aminullah; Hefny (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This research aims to explore the role of strategic leadership in driving change and innovation in Islamic educational institutions, focusing on the policies and implementation of changes implemented by madrasah heads. This study uses a qualitative approach with a case study design, which involves in-depth interviews with madrasah heads, administrative staff, and senior teachers, as well as direct observation of the learning process and policies implemented. The findings of the study show that madrasah heads play an important role in directing change through policies that focus on improving the quality of technology-based education, despite constraints such as limited resources and facilities. Administrative staff expressed the importance of technology-based management systems to improve operational efficiency, while teachers suggested continuous training in order to optimize the use of technology in learning. Students felt motivated by technology-based changes, despite difficulties in accessing learning materials due to internet access constraints. The study also identified that although there are policies that support innovation, their implementation is still hampered by limited facilities and adequate training. Therefore, improved technology facilities, intensive training for teachers, and increased access for students are needed to ensure successful policy implementation. Overall, this research provides insight into the importance of strategic leadership in managing change and innovation in Islamic education, as well as the challenges that need to be addressed to achieve more quality and sustainable education.